The Impact of Remote Work and Leadership on the Vietnamese Banking Sector After the Pandemic - Phuong Loan, Huynh Thi (Global journal of Business and Integral Security, 2024)
This research investigates the impacts of remote working on organisational performance in the banking industry in Vietnam after the Covid-19 pandemic. An online survey was conducted and 120 valid responses were collected. Using PLS-SEM, it is found that remote work has a significant positive impact on employee performance, which positively influences the organisational performance of banks in Vietnam. This is aligned with previous studies on remote work in other industries and countries. However, the moderating effects of company policy and transformational leadership on the correlation between remote work and employee performance are not supported in this research. These findings contradict previous studies and indicate a lack of company policy and leadership in support of remote work implementation.